The Economic And Social Context For The Changes In Accident Compensation - Stephens, Robert (Victoria University of Wellington Law Review, 2003)
The changes in ACC after 1980 cannot be separated from profound changes in the shape and direction of New Zealand’s political economy. Responding initially to the inherited economic imbalances in the 1970s, after 1984 the governing Labour Party launched a major restructuring of the economy and state administration. This paper describes the theories and objectives behind that transformation, as well as the generally disappointing results for economic performance and social equity. Further erosion of confidence in the state and dedication to market-driven policies continued well into the 1990s under the National Party. This paper documents the major trends during this entire period for employment, productivity, social inequality, and poverty.